The Dry - Harper, Jane (Jane Elizabeth) (New York : Flatiron Books, 2017)
" One of the most stunning debuts Ive ever read . . . Every word is near perfect. -- David Baldacci. A small town hides big secrets in The Dry, an atmospheric, page- turning debut mystery by award-winning author Jane Harper. After getting a note demanding his presence, Federal Agent Aaron Falk arrives in his hometown for the first time in decades to attend the funeral of his best friend, Luke. Twenty years ago when Falk was accused of murder, Luke was his alibi. Falk and his father fled under a cloud of suspicion, saved from prosecution only because of Lukes steadfast claim that the boys had been together at the time of the crime. But now more than one person knows they didnt tell the truth back then, and Luke is dead. Amid the worst drought in a century, Falk and the local detective question what really happened to Luke. As Falk reluctantly investigates to see if theres more to Lukes death than there seems to be, long-buried mysteries resurface, as do the lies that have haunted them. And Falk will find that small towns have always hidden big secrets. "--
Booklist
Kirkus Reviews
Publishers Weekly
BookPage
Adult.
Adult.
Keywords: Homecoming -- Fiction; Best friends -- Death; Fiction; Homicide investigation -- Fiction; Truthfulness and falsehood -- Fiction; Secrecy -- Fiction; Australia -- Officials and employees; Fiction; Australia -- Fiction; Mystery fiction; Suspense fiction